Pemilihan Daerah Penerima Bantuan Logistik Menggunakan Metode Simple Additive Weighting (SAW) - Iis Juniarto; Ady Widjaja (Teknik Informatika Universitas Pamulang, 2020)
Deputy for Logistics and Equipment is a unit that handles requests for logistical assistance along with equipment in areas that need assistance related to disasters that occur. Provision of Logistics Assistance so far there are still some obstacles including the process of calculating each region that proposes logistics assistance is done with a simple calculation and using microsoft excell and aspects calculated only based on disaster-prone categories without taking into account other aspects. So that areas that really deserve logistical assistance become unable to get help. The solution to the problem is to use Simple Additive Weighting (SAW) algorithm that is applied to a decision support system. The results of the study in the form of a decision support system and the results of the system output showed that the recipient area was Aceh which was chosen with a score of 81.17.